Quantum mechanical calculation of Rydberg–Rydberg autoionization rates. (6th October 2016) - Kiffner, Martin; Ceresoli, Davide; Li, Wenhui; Jaksch, Dieter
Abstract: We present quantum mechanical calculations of autoionization rates for two rubidium Rydberg atoms with weakly overlapping electron clouds. We neglect exchange effects and consider tensor products of independent atom states forming an approximate basis of the two-electron state space. We consider large sets of two-atom states with randomly chosen quantum numbers and find that the charge overlap between the two Rydberg electrons allows one to characterise the magnitude of the autoionization rates. If the electron clouds overlap by more than one percent, the autoionization rates increase approximately exponentially with the charge overlap. This finding is independent of the energy of the initial state.